A Comparative Analysis PT Mitra Adiperkasa, Tbk of the Pandemic's Impact on Similar Businesses in the Retail Sector - Kresnanda Ali; Asep Darmansyah (Universitas Bina Sarana Informatika, 2025)
The primary objective of this study is to analyze how the pandemic has affected key financial indicators, including liquidity, solvency, profitability, and activity ratios of PT Mitra Adiperkasa, Tbk. The research utilizes quantitative methods, employing ratio analysis, vertical analysis, and horizontal analysis as comprehensive assessment tools. Furthermore, a comparative analysis with PT Mitra Adiperkasa, Tbk is conducted to measure the extent of pandemic effects on similar businesses in the retail sector. The research data source was derived from the financial statements of PT Mitra Adiperkasa Tbk (MAPI) during the period 2018-2022. The data is further supported by secondary sources such as annual reports, publications from the Central Bureau of Statistics. The findings of the study reveal a dynamic financial journey characterized by growth, challenges, and recovery. Prior to the pandemic, PT Mitra Adiperkasa, Tbk. experienced positive growth in sales revenue and total assets, but faced difficulties in key financial metrics. The pandemic resulted in a decline in sales revenue, total equity, and net income, presenting significant profitability challenges. However, the company demonstrated resilience and adaptability, bouncing back with increased sales revenue, total assets, and net income in the post-pandemic period. The findings have practical implications for companies seeking strategies to enhance financial stability and operational efficiency amidst ongoing challenges.